Determinants of retention strategies for health care practitioners in public health facilities in Kenya: a case of County Hospitals in Nairobi Kenya - Kamaara, Sheila Nduta (Strathmore University, 2018)
At the heart of each and every health care system, the workforce is central to advancing health. Healthcare is a labour- intensive industry and therefore retention and growth of is important. This study seeks to determine the retention strategies used by public health facilities where brain drain has become rampant in the facilities. The study sought to determine the retention strategies by looking at the following three aspects of the facilities. First the study looked at the relationship between the motivation strategies used and how they influenced staff retention in the public health facilities. Secondly, the study looked at the relationship between employee relations management strategies adopted to enhance the retention of healthcare practitioners in Kenya. Thirdly, the study focused on the professional growth strategies that are in place and how they influenced retention of healthcare practitioners in the public healthcare facilities. The study was based on various theories on employee behaviors such as the Expectancy theory and Maslow’s Theory. To achieve these objectives, the data was collected at the 3 County hospitals in Nairobi County (Mama Lucy Kibaki Hospital, Mbagathi County hospital and Pumwani Maternity Hospital) where a sample of 165 respondents was drawn using simple random sampling method. Primary data was collected using a semi structured questionnaire. Data was analyzed using SPSS (Version 20.0). Basic descriptive statistics were used as well. The data was then analyzed through percentages, frequencies, mean, standard deviation and inferential statistics. The findings were presented in tables, graphs and narratives for easy comparison. The study found out that all the variables had a positive and significant influence on employee retention. Motivation strategies had a significant influence on employee retention as shown by the coefficient (β = 0.365, t = 4.433, p> 0.000). Employee relations management strategies also showed a significant influence on employee retention with the coefficients (β = 0.168, t = 32.132, p> 0.005) indicating a positive effect employee retention. Professional growth strategies as well showed a significant influence with a coefficient of (β = 0.309, t = 3.781, p> 0.000) showing a positive and significant relationship. The study concluded that the hospital supervisors should usually discuss issues affecting employees with them and other employees and mentor and coach them. The study recommended that the hospitals should have a clear career development plan for their employees which improve their retention.
Keywords: Health care system; Public health facilities; Motivation strategies; Advancing health